Oral mucosal lesions in patients with SARS-CoV-2 infection. Report of four cases. Are they a true sign of COVID-19 disease? (2020)
Background Vesiculobullous and macular lesions in the oral mucosa have been reported in patients positive for SARS‐CoV‐2 infection. Nonetheless, the significance and physiopathology of oral manifestations have not been clearly established in the clinical progression or outcome of the infection. Aim To describe the clinico‐pathological oral mucosal lesions in four patients with confirmed SARS‐CoV‐2 infection. Methods and Results Four patients with COVID‐19 disease and confirmed by polymerase chain reaction (PCR) presented angina bullosa hemorragica‐like lesion, vascular disorder, and nonspecific stomatitis, one patient with histological analysis demonstrated perivascular reactive lymphocitic infliltrate, focal capillary thrombosis, and hemorrhage. According to the discrimination of other local and systemic conditions and the synchronous onset of oral and systemic symptoms, the diagnosis of oral lesions probably associated with COVID‐19 was established. Conclusion Infection with SARS‐CoV‐2 may result in oral manifestations with various clinical presentations, which presumably support the hypothesis of thrombi formation and vasculitis; nevertheless, these findings need more evidence and a long‐term follow up of patients to accurately establish the significance of the oral mucosa affection in the COVID‐19 disease.